Discussing physical restrictions in care plan meetings between family members of residents with dementia and nursing home staff - Paananen Jenny; Lindholm Camilla (SAGE PUBLICATIONS LTD, 2025)
In long-term dementia care, caregivers face a dilemma. On the one hand, they need to respect the residents' right to self-determination, but on the other hand, they sometimes rely on physical restraints to deal with potential violence and self-destructive behavior. The issue of self determination is further complicated by residents often depending on family members as advocates in decision-making. In this article, we examine 15 care plan meetings to identify the professional practices of discussing the physical restrictions posed to residents with severe dementia. Our method is conversation analysis. Our analysis demonstrates that staff members' practices involve informing, accounting, and agreeing on the goals rather than on the methods of physical restraining. Staff members tend to first inform family members about the principles of restraining and then account for the use of restraints. Accounts highlight the problems that can be avoided and the benefits that can be achieved by limiting residents' actions. Consequently, the family members' role in the discussion is to accept the decision that has already been approved by authorities. As the staff members highlight the aim of protecting the well-being of the resident, the family members tend to respond with overt agreement and even promote the use of restraints. Current negotiation practices provide insufficient opportunities for family members to advocate for residents. Therefore, we recommend involving family members in decision-making about restraining at an earlier stage, adjusting the protocol in care plan meetings, and engaging the family in minimizing and preventing restraints. In general, staff members should pay more attention to the residents' experiences and the family members' lifeworld knowledge of the residents.